Multi-residue pesticide analysis in chicken: LC-MS/MS method development and validation - AISHWARYA S NAIR; VILAS M VAIDYA; RAVINDRA J ZENDE; SNEHALATA P KAMBLE; SMITA S GHULE; PRANJALI M DESAI (Indian Journal of Animal Sciences)
The presence of pesticide residue in meat has been of great public health significance. In order to address the existing gap in the literature, a rapid and sensitive method was standardised and validated to detect and quantify multi-residue pesticides in animal origin food. Thus, a highly sensitive method based on modified QuEChERS (quick, easy, cheap, effective, rugged and safe) extraction coupled with Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS) analysis has been standardised and validated to determine simultaneously 20 selected pesticide residues in chicken. The developed method is satisfactory in terms of accuracy (relative recoveries range between 73.26 to 116%) and sensitivity (limits of detection in the range of 4.41 to 5.86 μg/kg). The method accuracy and precision (RSD≤20%) complied with performance criteria of the SANTE/11312/2021 analytical quality control procedure. The application of validated methodology to chicken samples collected from retail shops and farms of Mumbai, Palghar, Thane, Satara and Pune districts of Maharashtra revealed the presence of trace levels of carbendazim at concentrations below the Maximum Residue Limit (MRL). The study of pesticide multi residues should be further explored along with regular monitoring and surveillance to ensure food safety and public health.